Structure and Electronic Properties of Point Defects at Semiconductor Oxide Interfaces - Mehes, Eric (Trinity College (Dublin, Ireland). School of Physics, 2015)
Semiconductor-oxide interfaces, particularly Si/SiO2 and Si/HfO2, are the centrepieces of transistor technology. Defects at such interfaces can massively affect device performance. Experimental studies on Si/SiO2 and Si/HfO2 interfaces accurately describe the structure of some of these defects, but the local atomic structure of others remains unknown. The exact positions of individual atoms at semiconductor-oxide interfaces can not yet be determined experimentally. Theoretical simulations are thus required to analyse the possible structural and electronic properties of the interface defects. This work aims to answer two questions: which defects appear in (001) Si/SiO2 and (001) Si/HfO2 interfaces and what states do such structure produce in the band gap region of the structures. For this a mix of molecular dynamics and density functional theory methods were used to generate valid interface structures. Recurring interface defects were identified. The contribution of these defects to the total density of states of the structure was determined. The most frequently occurring defect in the oxide layer of Si/SiO2 interface structures were E0-type structures such as the ones previous studies observed in bulk SiO2. The two recurring interface defects observed in this study were a dangling bond on a (2 × 1) (001) Si dimer reconstruction (dimer defect) and a threefold coordinated Si bonded to two substrate Si and one O from the oxide layer (“broken dimer” defect). Hydrogen passivation is extremely effective in removing the gap states of E’ and dimer type defects, and moderately effective in removing the gap states caused by “broken dimer” defects.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin